A diagnostic dilemma between psychosis, neuroleptic malignant syndrome and encephalitis. (February 2012) - Verma, Anupam; Ruttley, Angharad
SUMMARY  We describe the case of a patient presenting with symptoms highly suggestive of a psychotic illness. Prior to an organic assessment, antipsychotics were commenced at an early stage, causing neuroleptic malignant syndrome and contributing to confusion regarding the pathophysiology and etiology of the presentation. The chronology of symptoms was suggestive of a disease process prior to neuroleptic malignant syndrome and investigations subsequently confirmed anti-NMDA receptor encephalitis. The picture was further complicated by considerable psychosocial stressors, which were thought to have been contributory to perpetuation of the presentation. The case highlights the importance of close working relationships between psychiatry and neurology, and also the consideration of both organic and psychiatric pathology when patients present.